Quality by Design Assisted Development of Fast Dissolving Buccal Film of Ivabradine - Kumar, Anushree Sunil; Reddy, Kavitha Arenur Narayana; Reddy, Rohith Narayana; Reddy, Kavya Shivashankar; Dang, Raman (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Buccal drug delivery is a novel drug delivery system ensure fast onset of action and avoids the first pass metabolism and ultimately improves the bioavailability. Aim The present investigation is oriented towards design and development of Fast Dissolving Buccal Film (FDBF) of Ivabradine HCl (BCS Class I drug) by applying Quality by Design (QbD) concept. Materials and Methods The Quality Target Product Profile was defined for the proposed formulation, CQA’s were identified and risk assessment was carried to identify the most critical factors associated with the formulation development. Main Effect Screening design was applied by using independent variable as HPMC and Kopulan-PG, PEG 400, Tween 80 as material attributes that have an impact on responses such as Folding endurance, Disintegration time, % Drug content and % Drug release at 15 min. The stability data obtained for the optimal formulation was computed in the JMP stability toolbox to predict the expiration date. Results The results of the main effect screening design of 12 formulations indicated that the combined action of three factors had a significant impact on Ivabradine release and could predict the ideal formulation with the necessary Quality target product profile (QTPP). The statistically significant models were determined for % drug release at 15 min (R2=0.97) disintegration time (R2=0.99), folding endurance (R2=0.99) and drug Content (%) (R2=0.98). The optimal formulation confirms the expiration date of 25 months. Conclusion The selected factors and responses have a strong association and are significant enough for formulation optimization, because the highest global desirability value obtained was 0.80.
Keywords: Ivabradine; Fast Dissolving Buccal Film; Quality by Design; HPMC; Kopulan PG. Risk Assessment